Functional phytochemicals in tomatoes: biosynthesis, gene regulation, and human health implications - ElShamey, Essam; Zeng, Yawen; Ding, Yumei; Yang, Jiazhen (Frontiers in Plant Science, 2025)
The nutritional and health-promoting properties of tomatoes (Solanum lycopersicum), a highly significant crop, are attributed to their abundance of beneficial components, such as flavonoids, phenolic compounds, and carotenoids (including lycopene and β-carotene). The occurrence of these bioactive molecules is influenced by genetic, environmental, and agronomic factors, with ripening playing a critical role in their accumulation. This abstract delves into the molecular machinery controlling phytochemical accumulation, with a specific focus on the regulation of lycopene biosynthesis. The RIPENING-INHIBITOR (RIN) transcription factor, a master regulator of fruit maturation, exerts direct control over lycopene accumulation by binding to the promoters of critical biosynthetic genes. RIN directly activates the expression of PHYTENE SYNTHASE 1 (PSY1), the key rate limiting enzyme committing metabolic flux to the carotenoid pathway, and PDS, encoding phytocene desaturase, thereby orchestrating the massive lycopene synthesis characteristic of the ripening transition. Strategies for the biofortification of tomato fruits have leveraged this understanding through targeted genetic manipulation. Overexpression of key enzymes, such as the bacterial CrtB (phytoene synthase) or manipulation of the endogenous PSY1, has successfully enhanced lycopene flux. More profoundly, the manipulation of transcription factors offers a powerful multi-gene approach. For instance, the overexpression of fruit-specific promoters driving RIN or other regulators like HYR (High Pigment) can simultaneously improve the entire pathway, leading to substantial increases in lycopene content. Flavonoids and phenolic compounds are produced by the phenylpropanoid pathway, which is regulated by enzymes such as chalcone synthase (CHS) and phenylalanine ammonialyase (PAL). Gene regulation of these pathways involves a complex interplay of transcription factors (e.g., RIN, NOR, and HY5) and phytohormones (e.g., ethylene and abscisic acid), which modulate expression patterns during fruit development and stress responses. Phytochemical levels are also significantly influenced by environmental factors; for instance, optimal lycopene synthesis occurs at 20-25 °C, while higher temperatures above 30 °C inhibit lycopene accumulation and promote beta-carotene synthesis, a shift mediated by the temperature-sensitive expression of key genes, including those regulated by RIN. Naturally occurring or induced mutations in genes such as DET1 and HP2, which are negative regulators of light signal transduction, result in high pigment phenotypes with dramatically increased lycopene and flavonoid content. The successful application of metabolic engineering and transcription factor manipulation for biofortification holds immense promises for developing next-generation tomato cultivars with amplified health-promoting properties, directly linking agricultural science to improved human health outcomes through the mitigation of chronic diseases like cancer and cardiovascular disorders.